2017
DOI: 10.4238/gmr16039774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Schizolobium parahyba var. amazonicum (Huber ex. Ducke) Barneby, in a forest area in Brazil

Abstract: Schizolobium parahyba var. amazonicum (Fabaceae) is an arboreal species, endemic to the Amazon Rainforest, popularly known as paricá. It is used on a commercial scale in the timber sector, pulp and paper production, reclamation projects in degraded and landscaped areas. However, there is no availability of genetically improved material selected for the environmental conditions of the State of Espírito Santo, Brazil. In this sense, the present study aimed to characterize the genetic diversity in a population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Giustina et al (2017) As little is known about the genetic variability of balsa wood, it is necessary to make comparisons with other similar species. Giustina et al (2017) identified dissimilarity values between 0 and 0.26 in commercial teak plantations, and Silva Júnior et al (2017) found dissimilarity values between 0.04 and 0.8 in Brazilian firetree forests.…”
Section: Resultsmentioning
confidence: 98%
“…Giustina et al (2017) As little is known about the genetic variability of balsa wood, it is necessary to make comparisons with other similar species. Giustina et al (2017) identified dissimilarity values between 0 and 0.26 in commercial teak plantations, and Silva Júnior et al (2017) found dissimilarity values between 0.04 and 0.8 in Brazilian firetree forests.…”
Section: Resultsmentioning
confidence: 98%
“…Inter Simple Sequence Repeats (ISSR) markers are commonly employed in genetic studies of forest populations to assess genetic diversity (Brandão, Vieira, Nazareno, & Carvalho, 2015;Silva Júnior, Souza, Pereira, Caldeira, & Miranda, 2017;Teixeira et al, 2020). They serve as a foundation for studies and programs aimed at producing seeds and clones of superior genetic quality.…”
Section: Introductionmentioning
confidence: 99%
“…Quando a população é pequena e a variação genética intrapopulacional é estreita, aumenta-se a possibilidade de cruzamentos consanguíneos, resultando na manifestação de depressão por endogamia e isso prejudica a capacidade da descendência da população em se adaptar às mudanças bióticas e abióticas (Ingvarsson & Dahlberg, 2018). Assim é desejável que tanto as áreas de coleta de sementes quanto às coleções de germoplasma usadas para melhoramento genético possuam alta diversidade genética (Pritchard et al, 2014;Silva-Júnior, Souza, Pereira & Miranda, 2017).…”
Section: Introductionunclassified